Відповідь:
Покрокове пояснення:
1180. (a-b)-(a-c)+(b-d)=a-b-a+c+b-d=c-d, якщо с=-115.3, d=-597,3, то -115,3-(-597,3)=-115,3+597,3=482
1181. 1) 7,4-(х-2,6)=19
7,4-х+2,6=19
10-х=19
-х=19-10
-х=9
х=-9
2) 4,3+(3,1-х)=12,7
4,3+3,1-х=12,7
7,4-х=12,7
-х=5,3
х=-5,3
3) 7,2-(2,9+х)=-19
7,2-2,9-х=-19
4,3-х=-19
-х=-23,3
х=23,3
4) -5,2+(у-4,2)=-9,4
-5,2+у-4,2=-9,4
-9,4+у=-9,4
у=0
5) 2/9-(1/9-х)=4 1/9
2/9-1/9+х=4 1/9
1/9+х=4 1/9
х=4
6) (х+7/15)-2/15=4 1/15
х+7/15-2/15=4 1/15
х+5/15=4 1/15
х=4 1/15-5/15
х=3 11/15
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
Покрокове пояснення:
1180. (a-b)-(a-c)+(b-d)=a-b-a+c+b-d=c-d, якщо с=-115.3, d=-597,3, то -115,3-(-597,3)=-115,3+597,3=482
1181. 1) 7,4-(х-2,6)=19
7,4-х+2,6=19
10-х=19
-х=19-10
-х=9
х=-9
2) 4,3+(3,1-х)=12,7
4,3+3,1-х=12,7
7,4-х=12,7
-х=5,3
х=-5,3
3) 7,2-(2,9+х)=-19
7,2-2,9-х=-19
4,3-х=-19
-х=-23,3
х=23,3
4) -5,2+(у-4,2)=-9,4
-5,2+у-4,2=-9,4
-9,4+у=-9,4
у=0
5) 2/9-(1/9-х)=4 1/9
2/9-1/9+х=4 1/9
1/9+х=4 1/9
х=4
6) (х+7/15)-2/15=4 1/15
х+7/15-2/15=4 1/15
х+5/15=4 1/15
х=4 1/15-5/15
х=3 11/15